An In Vitro Study on the Cytotoxicity and Genotoxicity of Silver Sulfide Quantum Dots Coated with Meso-2,3-dimercaptosuccinic Acid - ÖZKAN VARDAR, Deniz (Turk J Pharm Sci, 2019)
OBJECTIVES: Silver sulfide (Ag(2)S) quantum dots (QDs) are highly promising nanomaterials in bioimaging systems due to their high activities for both imaging and drug/gene delivery. There is insufficient research on the toxicity of Ag(2)S QDs coated with meso-2,3-dimercaptosuccinic acid (DMSA). In this study, we aimed to determine the cytotoxicity of Ag(2)S QDs coated with DMSA in Chinese hamster lung fibroblast (V79) cells over a wide range of concentrations (5-2000 μg/mL). MATERIALS AND METHODS: Cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and neutral red uptake (NRU) assays. The genotoxic and apoptotic effects of DMSA/Ag(2)S QDs were also assessed by comet assay and real-time polymerase chain reaction technique, respectively. RESULTS: Cell viability was 54.0±4.8% and 65.7±4.1% at the highest dose (2000 μg/mL) of Ag(2)S QDs using the MTT and NRU assays, respectively. Although cell viability decreased above 400 μg/mL (MTT assay) and 800 μg/mL (NRU assay), DNA damage was not induced by DMSA/Ag(2)S QDs at the studied concentrations. The mRNA expression levels of p53, caspase-3, caspase-9, Bax, Bcl-2, and survivin genes were altered in the cells exposed to 500 and 1000 μg/mL DMSA/Ag(2)S QDs. CONCLUSION: The cytotoxic effects of DMSA/Ag(2)S QDs may occur at high doses through the apoptotic pathways. However, DMSA/Ag(2)S QDs appear to be biocompatible at low doses, making them well suited for cell labeling applications.